WHO GAINS FROM SOCIAL ASSISTANCES? RASTRA, PIP, AND PKH PROGRAMS IN INDONESIA - Abrian Duta Firmansyah; Akhmad Solikin (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2019)
Social assistance is one of government’s strategies in alleviating poverty and reducing inequality. This article analyses impact of social assistances in terms of Prosperous Rice (Beras Sejahtera, Rastra), Indonesia Intelligent Program (Program Indonesia Pintar, PIP), and Family Hope Program (Program Keluarga Harapan, PKH) on poverty and inequality, and problems related to implementation of these programs. Impact analysis was carried out using the benefit incidence analysis by using household surveys (Susenas) data March 2017, while problems in the fields were collected from literature and mass media analyses. The results indicate that social assistances in Indonesia impacted on alleviating poverty and reducing inequality, as well as absolute progressive in nature. Rastra is the most able to reduce poverty and equality compared to PKH and PIP. However, further improvements are needed to overcome the leakage in the distribution of social assistances. Literature and mass media reviews showed that data on recipients of social assistances were not up to date and disbursement of assistances violated existing regulations.